Crystallization and preliminary X-ray diffraction analysis of the high molecular weight ketoacyl reductase FabG4 complexed with NADH - Dutta, Debajyoti (International Union of Crystallography, 2012)
FabG4 from Mycobacterium tuberculosis belongs to the high molecular weight ketoacyl reductases (HMwFabGs). The enzyme requires NADH for β-ketoacyl reductase activity. The protein was overexpressed, purified to homogeneity and crystallized as a FabG4–NADH complex. A mountable FabG4:NADH complex crystal diffracted to 2.59 Å resolution and belonged to space group P1, with unit-cell parameters a = 63.07, b = 71.03, c = 92.92 Å, α = 105.02, β = 97.06, γ = 93.66°. The Matthews coefficient suggested the presence of four monomers in the unit cell. In addition, a self-rotation function revealed the presence of two twofold NCS axes and one fourfold NCS axis. At χ = 180° the highest peak corresponds to the twofold NCS between two monomers, whereas the second peak corresponds to the twofold NCS between two dimers.